Peran Lingkungan Religius TPA An-Nur dalam Pembentukan Identitas Keagamaan Anak Usia 7–12 Tahun - Yokha Latief Ramadhan; Aida Raihani Subandi (Medan Resource Center, 2024)
This study aims to explore how the religious environment of TPA An-Nur influences the formation of religious identity in children aged 7 to 12. Religious identity plays a crucial role in a child's personality development, encompassing the internalization of spiritual values and their expression in daily behavior. Using a qualitative approach with a case study design, the research involved six purposively selected children as main participants, along with TPA teachers as supporting informants. Data were collected through participatory observation, in-depth interviews, and document analysis. Thematic analysis was conducted based on Henri Tajfel’s social identity theory. The findings reveal that the religious environment of TPA significantly contributes to shaping children's religious identity through processes of social categorization, group identification, and the internalization of Islamic values. Elements such as peer and teacher interactions, worship routines, religious symbols, and hidden curriculum work together to build an authentic and sustainable religious identity. Children’s religious identity is reflected in their conceptual understanding of Islamic teachings, spiritual engagement, and daily practice of religious values. This study offers a theoretical contribution to the field of the psychology of religion and serves as a practical reference for enhancing religious education in non-formal settings